Long-term dynamics of plant communities after biological remediation of oil-contaminated soils in far north - A. B. Novakovskiy (Nature Portfolio, 2021)
Abstract We studied the long-term dynamics of plant communities after bio and phytoremediation of oil-polluted soils. Nine plots located in European Northeast and treated using various bioremediation methods were monitored from 2002 to 2014. Geobotanical descriptions (relevés) of each plot were performed in 2006 and 2014, and Grime’s theoretical CSR (competition–stress–ruderality) framework was used to assess the vegetation state and dynamics. We observed a clear shift of communities from pioneer (where ruderal species were prevalent) to stable (where competitor species were dominant) states. However, the remediation type did not significantly impact the vegetation recovery rate. After 12 years, all methods led to a 55–90% decrease in the oil content of the soil and a recovery of the vegetation cover. The plant communities contained mainly cereals and sedges which significantly differed from the original tundra communities before the oil spill. The control plot, treated only by mechanical cleaning, had minimum oil degradation rate (50%) and vegetation recovery rates, although, in CSR terms, its vegetation assemblage resembled the background community. Cereals (Agrostis gigantea, Deschampsia cespitosa, Phalaris arundinacea, and Poa pratensis), sedges (Carex canescens, Carex limosa, and Eriophorum vaginatum), and shrubs (Salix) were found to be the most effective species for phytoremediation, exhibiting high community productivity under the harsh northern conditions.